2018
DOI: 10.1111/nyas.13664
|View full text |Cite
|
Sign up to set email alerts
|

Driving working memory with frequency‐tuned noninvasive brain stimulation

Abstract: Frequency-tuned noninvasive brain stimulation is a recent approach in cognitive neuroscience that involves matching the frequency of transcranially applied electromagnetic fields to that of specific oscillatory components of the underlying neurophysiology. The objective of this method is to modulate ongoing/intrinsic brain oscillations, which correspond to rhythmic fluctuations of neural excitability, to causally change behavior. We review the impact of frequency-tuned noninvasive brain stimulation on the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 109 publications
(257 reference statements)
5
12
0
1
Order By: Relevance
“…The fMRI results in all participants during the encoding of the tonal memory task (as compared with silence, Figure 1c) revealed a classic pattern of activity in bilateral auditory and right inferior frontal cortices (see Supporting Information Table S2 and Supporting Information Figure S2). This activation pattern is in line with recent studies showing the role of these regions, together with functional and effective connectivity between them, in online maintenance and integration of sequential auditory events (Albouy et al, , 2017Albouy et al, 2018;Albouy, Mattout, et al, 2013;Foster & Zatorre, 2010;Kumar et al, 2016;Zatorre et al, 1994). In addition to the auditory cortices and inferior frontal regions, activity emerged in bilateral frontal regions including the DLPFC and IFG during maintenance of tonal and verbal materials.…”
Section: Distributed Network Supporting Encoding and Maintenance Osupporting
confidence: 90%
See 1 more Smart Citation
“…The fMRI results in all participants during the encoding of the tonal memory task (as compared with silence, Figure 1c) revealed a classic pattern of activity in bilateral auditory and right inferior frontal cortices (see Supporting Information Table S2 and Supporting Information Figure S2). This activation pattern is in line with recent studies showing the role of these regions, together with functional and effective connectivity between them, in online maintenance and integration of sequential auditory events (Albouy et al, , 2017Albouy et al, 2018;Albouy, Mattout, et al, 2013;Foster & Zatorre, 2010;Kumar et al, 2016;Zatorre et al, 1994). In addition to the auditory cortices and inferior frontal regions, activity emerged in bilateral frontal regions including the DLPFC and IFG during maintenance of tonal and verbal materials.…”
Section: Distributed Network Supporting Encoding and Maintenance Osupporting
confidence: 90%
“…The pitch memory deficit is associated with delayed magnetoencephalographic responses in bilateral IFG and superior temporal gyrus (STG) during the encoding of melodies and right‐lateralized functional anomalies in the DLPFC and PPC during the maintenance of the melodic information in short‐term memory (Albouy, Mattout, et al, ). These results highlight deficits in the pitch perception and memory network described in typical individuals (Albouy et al, ; Albouy, Baillet, & Zatorre, ; Kumar et al, ; Zatorre et al, ) and are in agreement with functional and anatomical anomalies observed in the amusic brain (see Peretz, for review). Anatomical abnormalities have been reported in the right IFG, amusics’ brains showing decreased white matter concentration associated with increased gray matter concentration in this region (Albouy, Mattout, et al, ; Hyde, Zatorre, Griffiths, Lerch, & Peretz, ), and in the right STG (Hyde et al, , see also Mandell, Schulze, & Schlaug, for abnormalities observed in the left hemisphere).…”
Section: Introductionsupporting
confidence: 83%
“…Rhythmic TMS and alternate current stimulation (tACS, a form of transcranial electrical stimulation) have been increasingly used in cognitive neuroscience to modulate brain oscillations in a frequency specific manner to drive network activity (and associated functions) by entraining ongoing brain oscillations or synchronizing neuronal networks (Romei et al 2016). This approach has already led to important developments in the understanding of the neural bases of cognitive functions (Albouy et al 2018). If reward is associated to specific oscillatory neural activity (Levy et al 2017;Marco-Pallarés et al 2015), brain stimulation may be used to boost oscillations associated with art-related appreciation (reward).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our meta-analysis also indicates the engagement of the right IFG while listening to pleasant music, which goes in line with the right-hemispheric dominance in music processing. Previous fMRI and MEG studies have implicated the right IFG in musical structure processing -responding to musically unexpected events (Koelsch et al, 2005;Tillmann et al, 2006Tillmann et al, , 2003-, and tonal working memory -while retaining, manipulating and retrieving tonal information (Albouy et al, 2018(Albouy et al, , 2017Foster and Zatorre, 2010b). Consistent with the importance of these structures for music processing, individuals suffering from amusia (a deficit in music perception and production abilities, particularly in pitch processing) present morphological brain anomalies both in white and grey matter concentrations in the right IFG (Albouy et al, 2013) and in the connectivity between the STG and the IFG (Loui et al, 2009).…”
Section: Auditory Cortical Regionsmentioning
confidence: 99%